A common but unknown disease; A case series study. (September 2021) - Raziani, Yosra; Salah Othman, Brwa; Raziani, Sheno
Abstract: Background: The present study is conducted to introduce a common disease of abdominal wall which has received less attention in scientific resources. In traditional medicine sources Some scholars believe that this condition occurs due to the movement of the abdominal muscle near the umbilicus or nave laterally movement of nave. Design: A case series study. Method: the study did not receive any funding. This study was a case series study. The study population was all patients who following repeated hospital visits did not improve, and for their last try, they visited a traditional clinic, and were diagnosed with umbilical hernia during a period of 5 months. Data were collected using demographic information questionnaire, and a complete health history taking. Results: nave sliding is an abdominal wall defect and gastrointestinal and psychological problems are listed as the most prominent sign and symptoms. higher body mass index and presence of a first-degree relative with the same problem could be a predictor factor. Conclusion: Nave sliding is a common disease that there are a few scientific literatures about it and needs more attention from clinicians to avoid false diagnoses and requires more academic research to clarify any ambiguous side about it to promote the treatment process in a more scientific and approved methods. Highlights: Nave sliding is an abdominal wall defect. gastrointestinal and psychological problems are listed as the most prominent sign and symptoms. Higher body mass index and presence of a first-degree relative with the same problem could be a predictor factor.